ANALISIS PENGARUH DAYA TARIK IKLAN, KUALITAS PESAN IKLAN, FREKUENSI PENAYANGAN IKLAN TERHADAP EFEKTIVITAS IKLAN TELEVISI MIE SEDAP (Survei Pemirsa Iklan Mie Sedap Pada Mahasiswa Kost di sekitar Kampus Undip, Tembalang) - Sufa, Faela; Munas, Bambang (Faculty of Economics and Business Diponegoro University, 2012)
Competition for the fast food industry, as well as competition PT Wingsfood in doing product marketing Mie Sedap through television advertising media by its competitors. In the present study will analyze the influence of advertising appeal, the quality of the message, and often an ad on the effectiveness of television advertising. Student population is used around campus UNDIP Kost in Tembalang, Semarang. With the criteria viewers use television advertising Mie Sedap boarding students in the sample place at Banjarsari and Sumurboto, Tembalang of 100 respondents, with random sampling method. The results showed that the advertising appeal, the quality of the message, and frequency of ads have a positive and significant impact on the effectiveness of advertising, either partially or simultaneously. With the acquisition of the largest coefficient of 0.383 for the effect of quality on the effectiveness of advertising messages. So a better quality of messages would increase the effectiveness of advertising. Thus PT Wingsfood must consider three factors are variable, especially in the variable quality of the message to produce an effective advertisement in accordance with the cost of which has been issued.